Hot corrosion characteristics of SrCeO3 as thermal barrier coating material - Sachin Raj P.V.; Kumaresh Babu S.P.; Saravana Kumar P.; Dhayalan R. (Next Materials)
This study investigates the thermal barrier and hot corrosion characteristics of SrCeO3, a perovskite-structured material, synthesized via the solid-state method using SrCO3 and CeO2 as precursors. The crystal structure was confirmed by x-ray diffraction (XRD), and the elemental composition matched theoretical values based on energy-dispersive spectroscopy (EDS). Thermal analysis showed that SrCeO3 is phase stable up to 1400ºC, with thermal conductivity lower than that of yttria-stabilized zirconia (YSZ), though the coefficient of thermal expansion was similar. Mechanical properties, including elasticity, hardness, and fracture toughness, were found to be inferior to those of YSZ. Additionally, SrCeO3 showed incompatibility with thermally grown oxide (TGO) layers, reacting with Al2O3 at high temperatures. Atmospheric plasma sprayed coatings of SrCeO3 showed minimal decomposition, with only trace amounts of Sr(OH)2 and CeO2 formed during spraying. The high-temperature corrosion behavior of SrCeO3 was examined in a 32 wt% Na2SO4 + 68 wt% V2O5 salt mixture and pure V2O5 at 900ºC for 30 h. In the salt mixture, Sr3V2O8 was the primary corrosion product, whereas SrV2O6 formed in pure V2O5. The Na2SO4 in the salt mixture increased the corrosive activity by enhancing V2O₅ reactivity. Importantly, no Ce-V-O corrosion product was observed, confirming that corrosion followed the Lewis acid-base principle.